Plant Pathological Terms - IPS, Editor (Indian Phytopathology, 2010)
This book, in my opinion, is a ‘must have’ for every person working in the field of plant pathology. Everywhere one looks, more information has been added increasing its usefulness. This comprehensive dictionary provides an essential reference for plant pathologists and agriculturalists at all levels, listing the authoritative information in easy language. More than 4100 entries, which include all terms, used in several branches like mycology, plant bacteriology, plant virology, plant disease, plant disease management especially fungicides, quarantine and trade, epiphytology, plant nematology and molecular plant pathology. Many existing entries were updated and expanded. This book placed a wide coverage of all entries helpful in all competitive examinations concerning plant pathology because it is quite helpful in understanding the fundamentals of these highly technical and intricate branches of agricultural sciences. The terms of various aspects have generally been defined in a concise manner except those which required more elaborate explanation. Overall, the book provides a wide-ranging resource for all those working in the discipline. This dictionary fills a gap in the plant pathology literature. The author deserves thanks for making such a dictionary available. It certainly will find a place on the desk of many phytopathologists and others who have to deal with plant diseases.